2011
DOI: 10.1523/jneurosci.3382-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

An Autocrine Neuronal Interleukin-6 Loop Mediates Chloride Accumulation and NKCC1 Phosphorylation in Axotomized Sensory Neurons

Abstract: The cation-chloride cotransporter NKCC1 plays a fundamental role in the central and peripheral nervous systems by setting the value of intracellular chloride concentration. Following peripheral nerve injury, NKCC1 phosphorylation-induced chloride accumulation contributes to neurite regrowth of sensory neurons. However, the molecules and signaling pathways that regulate NKCC1 activity remain to be identified. Functional analysis of cotransporter activity revealed that inhibition of endogenously produced cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…This could be related to an increased volume necessary for fast elongation. Interestingly, we reported that nerve injury induced activation of the volume regulatory co-transporter Na + -K + -2Cl − that could account for volume increase in neurites thereby contributing to growth velocity [12], [13]. This size increase is compatible with our observation that growth cones become much softer than those from control neurones.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This could be related to an increased volume necessary for fast elongation. Interestingly, we reported that nerve injury induced activation of the volume regulatory co-transporter Na + -K + -2Cl − that could account for volume increase in neurites thereby contributing to growth velocity [12], [13]. This size increase is compatible with our observation that growth cones become much softer than those from control neurones.…”
Section: Discussionsupporting
confidence: 88%
“…In vitro , the neurons conditioned by the first traumatism display a faster, elongated mode of neurite growth called regenerative growth [10], [11]. This provides a convenient model to decipher post-transcriptional molecular adaptation involved in regenerative growth [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…An increased activity of NKCC1 and a depolarizing shift of E GABA in DRG neurons have been observed after nerve injury in several studies13142931. However, the net effect of the depolarizing shift of E GABA remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6R, soluble IL-6R, and gp130 are expressed in the cornea, 57 and the gp130 receptor is thought to be ubiquitously expressed in sensory neurons. 60 Thus, we speculate that the mechanism of corneal nerve regression after infection might involve direct action of local IL-6 on cells present in the cornea (resident and/or infiltrating immune cells), and/or IL-6 triggered signaling within sensory neurons innervating the tissue. Whether HSV-1 infection of sensory neurons in the trigeminal ganglia plays a role in the degeneration of corneal nerves remains unknown and should be further explored.…”
Section: Hsv-1 Inflammation and Corneal Nervesmentioning
confidence: 94%